GUIDELINES FOR THE PROCESS OF CROSS-CULTURAL ADAPTATION AND TRANSLATION OF THERAPEUTIC MODULES - Qamar, Tania; Ibrahim, Nabisah (Journal of Ayub Medical College Abbottabad, 2024)
Background: Language is a very important aspect for the adaptation and translation process. For many people, their native language is not just a means of communication but a vessel of cultural identity and emotional expression. When individuals are experiencing the difficulties of life, they should have the chance to address them using a language that truly connects with their personal experiences. Adapting and translating therapeutic modules to align with cross-cultural settings is important to ensure effectiveness and practicality among different populations. The objective of this article is to provide the guidelines for the process of cross-cultural adaptation and translation-back-translation of the therapeutic modules, and also provide the guidelines to test the reliability and validity of the translated version of therapeutic modules. Method. The Back-to-Back translation model (10) was used in this study for the guidelines of adaptation and translation of therapeutic modules. Following the instructions in this document made the process of adaptation and translation simpler. Results. Results showed that the (10) is a significant model and provided a systematic and comprehensive way for adaptation and translation of therapeutic module with make little changes in reaction to feedback and cultural awareness. Conclusion. At the end, it emphasised how important it is to conduct an extensive study to determine the effectiveness and cultural compatibility of the updated modules. However, these principles ultimately enhance effective and inclusive health care, providing health professionals with a foundation for adapting and translating therapeutic processes to diverse cultural conditions.